UNDERGRADUATE STUDENTS’ PERCEPTIONS AND ATTITUDES TOWARDS A CAREER IN TOURISM INDUSTRY: THE CASE OF INDONESIA - Muhammad Iqbal Rosyidi (Jurnal Manajemen dan Kewirausahaan, 2021)
As a world-class tourism destination, Indonesia is facing challenges in providing competent tourism human capital. Currently, the majority of tourism labor in Indonesia are low levels of education and only a few of them are graduated from higher education. Empirically, numerous studies suggest that many graduates from various tourism schools in several countries preferred to not opt for the tourism careers. This study aims to discover and analyze the perceptions and attitudes of final year students majoring in tourism and hospitality in Indonesia to pursue a career in the tourism industry. Using online distributed questionnaire through snowball sampling method, this study obtained 422 completed responses of tourism and hospitality undergraduates from Jakarta, Bandung, Lombok, Makassar, Palembang, Bali, Yogyakarta, Surakarta, and Batam. The collected data then analyzed by Importance Performance Analysis and cross-tabulation analysis. This study found that the career advancement and salaries were two factors in the industry considered as important factors but got a bad perception.  However, the nature of work of tourism industry which offering enjoyable and fun environment are considered important and earned positive perception. This study also presents some implications, mainly for the tourism industry in Indonesia.